Development and characterization of floating spheroids of atorvastatin calcium loaded NLC for enhancement of oral bioavailability. (17th August 2016) - Sharma, Kritika; Hallan, Supandeep Singh; Lal, Bharat; Bhardwaj, Ankur; Mishra, Neeraj
Abstract : Objective: The obejctive of the present study was to investigate the potential use of floating spheroids of Atorvastatin Calcium (ATS) Loaded nanostructured lipid carriers (NLCs). Materials and Methods: The final formula of floating spheroids was optimized on the basis of shape (spherical), diameter (0.47 mm), lag time (20 s), and floating time (> 32 h). Results: The results were further confirmed by different pharmacokinetic parameters—it was observed that the developed optimized floating ATS spheroid-loaded NLCs formulation has significantly improved relative bioavailability, that is, 3.053-folds through oral route in comparison to marketed formulation.